(untitled) (Acta Scientiarum. Biological Sciences, 2017)
This research aimed to analyze socio-environmental practices related to the conscious consumption of students of Sertão Pernambucano. A total of 174 high school students from two public schools were interviewed through a 29-item Likert-type measurement scale with five response levels. Among the students, 62.4% were female and 37.6% were male, aged between 15 and 20 years. It was found that 5.8% of the students were careful to take into account if the product residues were recyclable, 40.0% showed indifference or little commitment to use as few shopping bags as possible and the minority (8.3%) of the students used to separate the waste by categories. 47.9% of the students affirmed to reuse draft paper and 55.9% save gift paper for future packaging. Few have the habit of watching (24.8%), talking to friends (12.9%) or alerting people (23.2%) about environmental problems or news. Therefore, Environmental Education, particularly, habits related to conscious consumption, needs to be inserted in the school context so that socio-educational actions become a daily practice, improving the expectations of future generations.